Reaching Social Impact Through Communicative Methodology. Researching With Rather Than on Vulnerable Populations: The Roma Case - Gómez, Aitor; Padrós, María; Ríos, Oriol; Mara, Liviu-Catalin; Pukepuke, Tepora (Frontiers in Education, 2019)
Communicative methodology has been acknowledged as having an impact at all levels: social, political and scientific. The social impact is achieved with the communicative methodology by involving the people or communities we intend to study from the beginning to the end of the research. There are positive benefits to those involved, which increases the impact. Therefore, the communicative methodology enhances the potential of stakeholders (including those traditionally excluded) for social transformation through the use of egalitarian dialogue. Additionally, those stakeholders co-lead the research and promote change in their own social environments because of their inclusion in all stages of the research process. The theoretical basis of the communicative methodology led to the assumption of postulates that enable social transformation. Researchers, taking into account the theoretical principles and postulates, interpret reality through dialogic knowledge while researching with vulnerable populations. This article illustrates how it is possible to attain social impact using the communicative methodology in diverse contexts and points out how the communicative organization of research and the communicative analysis of data can be decisive in attaining social impact. Such change contributes to the social and educational transformation of reality and to improving the lives of vulnerable populations.